The analysis of the gut microbiome during liver disease progression led to the identification of biomarkers for related mild cognitive impairment - Giner-Pérez, Lola; Gallego, Juan-José; Gimènez-Garzó, Carla; Batallas, Daniela; Jarquín-Díaz, Víctor H.; Casanova-Ferrer, Franc; Fiorillo, Alessandra; Urios, Amparo; Martínez-Medina, Jennifer N.; López-Gramaje, Adrià; Arenas, Yaiza M.; Escudero-García, Desamparados; et al. (Frontiers in Microbiology, 2025)
IntroductionAlthough it is well established that liver disease is associated with alterations in the gut microbiome (GM), the mechanisms linking these microbial changes to the progression of liver disease—and more critically, to its related cognitive impairment—remain poorly understood. Therefore, to define biomarkers for the early and advanced phases of these conditions, it is necessary to gain insight into changes in the GM throughout the evolution of the disease, particularly regarding the early onset of cognitive decline.MethodsThe GM taxonomy and function profiles were defined, data were collected for dietary intake, fecal short-chain fatty acids (SCFA), cognitive status, quality of life and biochemical and immunological blood parameters of patients belonging to different stages of liver disease (MASLD and cirrhosis) and cognitive function.ResultsThis study showed: 1) the fibrosis stage severity (F1 to F4) in liver disease was associated with reduced GM diversity independently of cognitive status and with a decline in beneficial autochthonous bacteria; 2) Streptococcus mutans and Allisonella histaminiformans could serve as potential biomarkers for NAFLD-associated mild cognitive impairment; 3) bacterial metabolic functions involved in sugar degradation and the breakdown of tryptophan and glutamate were downregulated and linked to CXCL13 plasma levels and neuroinflammation; 4) correlations between SCFA concentrations disappeared with liver disease and cognitive impairment.ConclusionIn this context, maintaining a balanced production of fecal SCFA is more important than individual concentrations. The downregulation of specific microbial metabolic pathways, along with the presence of certain bacterial species, holds promise as early-stage biomarkers and highlights the potential of microbiome-targeted strategies for monitoring and managing liver-related cognitive impairment.